1999
DOI: 10.1007/s004320050284
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic assessment of brain tumours and non-neoplastic brain disorders in vivo using proton nuclear magnetic resonance spectroscopy and artificial neural networks

Abstract: The present data show the clinical utility of non-invasive 1H MRS by automated ANN analysis in the diagnosis of tumour and non-tumour cerebral disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 29 publications
(34 reference statements)
0
43
0
Order By: Relevance
“…Potential roles have been identified in pre-surgical diagnosis of tumour type and grade (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), monitoring of treatment response (20), and evaluation of tumour recurrence (21). However, optimised MRS analysis is required to enable the widespread clinical use of the technique.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Potential roles have been identified in pre-surgical diagnosis of tumour type and grade (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), monitoring of treatment response (20), and evaluation of tumour recurrence (21). However, optimised MRS analysis is required to enable the widespread clinical use of the technique.…”
mentioning
confidence: 99%
“…However, optimised MRS analysis is required to enable the widespread clinical use of the technique. Pattern classification of MRS data alone or in combination with MRI features has proven successful for accurately classifying brain tumours (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Although brain tumours are the most common solid tumours in children and a major cause of childhood mortality, they are rarer than in adults, and only small numbers have been reported in the few studies using MRS to discriminate paediatric brain tumours (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The potential diagnostic and prognostic capabilities of 1 H-MRS in brain tumours have received consider-able attention (Tedeschi et al, 1997;Nelson et al, 1999;Poptani et al, 1999;Preul et al, 2000). It would be reasonable to expect that morphological and clinical responses are preceded by a change in the tumour biochemistry.…”
mentioning
confidence: 99%
“…Introduction Recent work has suggested that magnetic resonance spectroscopy (MRS) may be useful in evaluating cancerous lesions [1]. MRS data have been obtained from a variety of body organs including the brain [2,3]. In a brain tumour resection, many (> 12) biopsy samples may be taken.…”
Section: Related Contentmentioning
confidence: 99%